2017
DOI: 10.3389/fpls.2017.02101
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis AGAMOUS Regulates Sepal Senescence by Driving Jasmonate Production

Abstract: The signal that initiates the age-regulated senescence program in flowers is still unknown. Here we propose for the ephemeral Arabidopsis thaliana flower that it dies because of continued expression of the MADS-box transcription factor AGAMOUS (AG). AG is necessary for specifying the reproductive structures of the flower. Flowers of ag-1, which lack AG, exhibited delayed sepal senescence and abscission. The flowers also had reduced jasmonic acid (JA) content. Other anther-defective sterile mutants deficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Our results may be due to a role of AG in the flower senescence pathway – partially agreeing with the study done by Jibran et al . (). Alternatively, the lack of developing ovules, and the presumed hormone‐driven sink function as seeds develop (Bennett et al ., ), would be lacking in sterile catkins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results may be due to a role of AG in the flower senescence pathway – partially agreeing with the study done by Jibran et al . (). Alternatively, the lack of developing ovules, and the presumed hormone‐driven sink function as seeds develop (Bennett et al ., ), would be lacking in sterile catkins.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Jibran et al . () reported that flowers of ag mutants showed delayed sepal senescence and abscission in Arabidopsis , which could be rescued by spraying jasmonate on plants. Contrary to these findings that low AG expression retarded or prevented senescence, we noticed accelerated flower senescence in several altered RNAi events (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Besides ethylene and auxin, JA affects abscission of fruits, leaves and flowers, independently from ethylene 74 77 . JA is known to promote senescence as well as abscission 78 81 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of TOE3 in flower patterning is not yet established [82]. Jibran et al (2017) proposed that AG functions not only in flower initiation, but also in flower development and senescence [87]. Binding AG to the ANTHER DEHISCENCE 1 (DAD1) promoter induces DAD1 gene expression to provide substrates for jasmonic acid (JA) biosynthesis.…”
Section: Age-related Senescence Pathways Need Microrna Actionmentioning
confidence: 99%
“…In a senescing flower, JA regulates stamen dehiscence, sepal yellowing, and perianth abscission. Such a phenomenon is postulated to be responsible for the ephemeral phenotype of Arabidopsis flowers [87]. Ephemeral flower senescence is independent of pollination and concurrent ethylene synthesis; thus, the flower lasts less than one day [88].…”
Section: Age-related Senescence Pathways Need Microrna Actionmentioning
confidence: 99%